Educate Children: Unleashing The Moral, Intellectual and Spiritual Dimensions in Enriching Children's Inner Repertoire and Creative Motivation [IQ, IE & IS] - Dewi, Niflach Mutiara; Fauziah, Nur (Universitas Muhammadiyah Surakarta, 2023)
Every wise parent wants their children to be smart and intelligent. The magnitude of these hopes and desires gave rise to the enthusiasm and concern of parents for the activities and efforts to educate their children's needs. The interesting thing is that it accommodates the harmonious relationship between parents, students and the school. Efforts to emphasize strong intelligence are on spiritual intelligence [Spiritual Intelligence]. With reliable spiritual values and intelligence, other aspects of intelligence, namely IQ and Emotional Intelligence (Emotional Intelligence) or IE, can be directed towards self-actualization of humans as servants of Allah and at the same time His caliphs on earth. Spiritual nuances that are developed in educating children increasingly give us confidence that the spiritual and religious values that we adhere to are